Multifunctionality of the verb devoir ‘must’ and falloir ‘need’ based constructions: a contrastive corpus-based study of French and Lithuanian - Valiukienė, Vita (Kalbotyra, 2016)
The present study examines the morphosyntactic features and functions of the constructionsje dois dire (que) ‘I must say (that)’ and (il) faut dire (que) ‘it is necessary to say (that)’ in French and their correspondences in Lithuanian. The study is corpus-based and the data have been retrieved from the bidirectional parallel corpus CTLFR-LT-FR. The thorough semantic functional analysis of the construction je dois dire (que) ‘I must say (that)’ in theCTLFR-LT shows that the verbs devoir ‘must’ and dire ‘say’ clearly express the meanings of necessity and saying. However, in initial position the construction with the complementizer que ‘that’ represents a lexical variant and may not be functionally transparent. Its functional indeterminacy may be clarified by its prosodic realizations. The conceptual meanings of the verbs devoir ‘must’ and dire ‘say’ in the construction je dois dire (que) ‘I must say (that)’ are bleached and the construction may function as a marker that initiates conversation with the addressee, expresses the author’s argumentation and links clauses or parts of discourse. In initial and medial position, it may hedge an utterance or modify a word or a phrase. Thus the construction je dois dire (que) ‘I must say (that)’ is not primary in the communicative structure of the sentence and functions as a marker of author stance. The construction (il) faut dire (que) ‘it is necessary to say (that)’ is less frequent in the CTLFR-LT and displays minor structural variation. It shows traces of parentheticalization, namely deverbalization (omission of the formal subject il), omission of the complementizer que ‘that’, syntactic mobility in the sentence, semantic bleaching of the verbs falloir ‘need’ and dire ‘say’, alternation with mental verbs (Pusch 2007), interpersonal and intertextual functions. The structure (il) faut dire + NP‘it is necessary + NP’ clearly expresses the meaning of necessity to say. The Lithuanian constructions turiu pasakyti/pripažinti ‘I must say/admit’ and reikia pasakyti/pripažinti ‘it is necessary to say/admit’ in the CTLLT-FR are not statistically significant and functionally they do not differ from the equivalent constructions in French. The data in the CTLFR-LT-FR and the CCLL (Contemporary Corpus of the Lithuanian Language) reveal that the constructions under study are not dominant either in French or Lithuanian but possible in authentic language use. Although the generalizations made above should be corroborated by more empirical data, the present study contributes to the research on parenthetical constructions in French and Lithuanian and can be supplemented by the analysis of the constructions in academic discourse.
Keywords: multifunctionality; parenthetical constructions; contrastive analysis; corpus-based study